2016
DOI: 10.1016/j.neuron.2016.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Tau Prion Strains Dictate Patterns of Cell Pathology, Progression Rate, and Regional Vulnerability In Vivo

Abstract: Summary Tauopathies are neurodegenerative disorders that affect distinct brain regions, progress at different rates, and exhibit specific patterns of tau accumulation. The source of this diversity is unknown. We previously characterized two tau strains that stably maintain unique conformations in vitro and in vivo, but did not determine the relationship of each strain to parameters that discriminate between tauopathies such as regional vulnerability or rate of spread. We have now isolated and characterized 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
420
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 375 publications
(444 citation statements)
references
References 42 publications
(83 reference statements)
23
420
1
Order By: Relevance
“…Next, because there is evidence to suggest that tau pathologies could transmit in a "straindependent manner" (4,33,41,42), and that tau mutants can cause tau to form conformationally distinct fibrils (43, 49), we sought to assess whether homotypic seeding may be more robust or necessary for some of the tau mutants to aggregate. The previous experiment was thus repeated, this time comparing heterotypic seeding with WT K18 tau fibrils to homotypic seeding with mutant K18 tau fibrils.…”
Section: Seeding Propensity Differs Significantly Among Ftdp-17 Tau Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, because there is evidence to suggest that tau pathologies could transmit in a "straindependent manner" (4,33,41,42), and that tau mutants can cause tau to form conformationally distinct fibrils (43, 49), we sought to assess whether homotypic seeding may be more robust or necessary for some of the tau mutants to aggregate. The previous experiment was thus repeated, this time comparing heterotypic seeding with WT K18 tau fibrils to homotypic seeding with mutant K18 tau fibrils.…”
Section: Seeding Propensity Differs Significantly Among Ftdp-17 Tau Mmentioning
confidence: 99%
“…Moreover, there is evidence to suggest that seeding occurs in a "strain-dependent" manner (4,33,41,42), and that individual mutations in tau may confer the ability to aggregate into conformationally distinct templates (43). Despite this, there is a lack of data in the field comparing the seeding propensities of multiple tau mutants and much of the current data utilizes specific mutants P301L and P301S, or truncated repeat domain (RD) tau (29,30,(44)(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%
“…it can be demonstrated that these different Tau conformers, when seeded in cultured cells expressing tau, induce the propagation of different "strains" of abnormal Tau aggregates (3). Furthermore, when these different tau species were re-inoculated into the brains of transgenic mice expressing mutant human tau protein, they induced different tau pathologies that resembled the aggregate patterns seen in patients with tauopathies (4,5). This suggests that individual tauopathies are associated with unique "strains" of the tau protein and provides an avenue for investigating how a single protein pathology can yield multiple disease phenotypes.…”
Section: Snapshots Of Neurodegenerative Diseasementioning
confidence: 93%
“…This is mainly due to the fact that prion diseases are transmitted from animals to humans or humans to humans. Interestingly, cadaver-derived human growth hormone containing neurodegenerative disease-associated proteins such as tau, Aβ and α-synuclein when injected into humans did not show any risk for Alzheimer's disease or Parkinson's disease in these recipients indicating the lack of transmissivity properties in these extracts [115,116]. This may also be due to the lack of potential seeding strains of tau or other proteins in these extracts or due to the lack of required incubation period for the disorders to manifest and mature.…”
Section: -175 D Pimentioning
confidence: 97%
“…Finally, Sanders et al [72] and Kaufman et al [115] elegantly demonstrated the presence of different tau strains in the brain of human tauopathies. Isolated tau strains from human tauopathies induced different forms of pathological aggregates in HEK293 cells.…”
Section: The Role Of Misfolded Tau In the Seeding And Propagationmentioning
confidence: 98%